Applications of heterogeneous computing in computational and simulation science. (1st January 2013) - Domanski, Luke; Bednarz, Tomasz; Gureyev, Timur; Murray, Lawrence; Huang, Bevan Emma; Nesterets, Yakov; Thompson, Darren; Jones, Emlyn; Cavanagh, Colin; Dadong, Dadong; Vallotton, Pascal; Sun, Changming; et al.
This paper presents a summary and overview of heterogeneous algorithms and applications developed by the Commonwealth Scientific and Industrial Research Organisation (CSIRO) for solving practical and challenging science problems such as: 1) high-content analysis of brain cell images for medical research and drug discovery; 2) genetic analysis of complex experimental designs for crop breeding; 3) solving computational fluid dynamics problems; 4) deconvolving 3D images from microscopy and medical imaging; 5) reconstructing large 3D computed tomography (CT) images from medical and materials science; 6) quantifying uncertainty in complex environmental models. Applications discussed utilise GPUs and multi-core CPUs on a scale ranging from single desktop workstations through to large GPU clusters. Results demonstrate that both types of system can successfully accelerate a variety of practical science applications. We have seen significant gains in productivity and opportunity as a result of leveraging GPUs, tackling computational problems in which execution time was previously infeasible.